Migrant issues in contemporary Japan - Adilgazinova, Aigerim (Dve domovini, 2024)
Japan has an interesting and ambivalent policy toward the migration process; therefore, it is interesting to examine the migration position of a mono-ethnic state, which has also had a history of “closure” and exclusion from the outside world. The research objective is to examine the characteristics of immigration processes in contemporary Japanese society. The research methods used include narrative, comparative, analytical, and structural. As a result, it can be argued that the legislative framework is important in dealing with migrants, which in Japan is recognized as highly effective; in general, the mechanism formed by the Japanese government for dealing with the migrant population copes with all its tasks. In the course of the work, the main problems of adapting to life in Japan were identified, which are the focus of the governing authorities.
Keywords: Asian labour market; delovne migracije; health insurance; labour migration; migracije; migracijska politika; migration; migration policy; social security; socialna varnost; trg dela; zdravstveno zavarovanje